EVALUATION AND STANDARDIZATION OF ESTONIAN OIL SHALE QUALITY CHARACTERISTICS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1997)
The most important mineral wealth of Estonia is oil shale, which is used as fuel for generating electricity, thermal energy, for producing the shale oil, impregnation oil, cement, concrete and other products.Estonian oil shale (Kukersite) deposit occupies an extensive territory (about of 1830 square km). Proved reserves in this deposit were estimated' about 4 billions tons of bil shale. (Fig. 1). The industrial oil shale seam (thickness 2,5 - 3,2 m) contains 6 "oil shale' layers (A - F2) which are separated from one other by limestone intercalation poor in kerogene. The calorific value of oil shale layers ranges between 7-15 MJTkg. The bedding depth of oil shale deposit is from a few meters up to 150 m, now maximum depth in mines are about 70 m. At present oil shale mining is carried out in 6 mines and 3 opencast, oil shale output was 14,6 million tons in 1996.The most important quality characteristics of oil shale are: calorific value Q, moisture W, ash content A, carbonic acid content C02, which have influence on efficiency of using oil shale in power and thermal processing plants and construction materials production. Therefore it is important to elaborate standards of oil shale quality, characteristics and investigate how to guarantine the required for consumers stable quality of oil shale. Checking necessary number of samples from mines, opencasts, power plants and. other consumers, evaluating precision of sampling and determination of quality characteristics is also important.